Conflitos Socioambientais, Educação Ambiental e Participação Social na Gestão Ambiental (Sustainability in Debate, 2011)
This is synthesis of the debates held during the round-table “Socioenvironmentalconflicts, environmental education and social participation on environmentalmanagement”, at the V ENANPPAS (2010), which has focused on the discussionof four main themes: Socioenvironmental conflicts and the myths of socialparticipation; Socioenvironmental conflicts and the uncertainty of conditions toenvironmental education immersed in problems and conflicts; Solution ofSocioenvironmental conflitcts ”“ actions mediated by instrumental rationality andemancipatory interest; Positive actions as dialogical-problematizing practice onconcrete reality. From an initial provocative text, each member has brought hisfirst contribution, followed by new questions as consequence of these speeches.The hole debate was recorded, transcripted and made a synthesis to present in thismanuscript form.